PICTURE STORYBOOKS ABOUT THE APPLICATION OF GOOD MORALS TO FELLOW FRIENDS AS AN EARLY CHILDHOOD EDUCATIONAL MEDIA - Mafaya, Yuna Salsabila; Fiyanto, Arif (LPPM Univ. Ibn Khaldun Bogor, 2025)
This design discusses the application of good morals to fellow friends through picture storybooks for early childhood, focusing on a book entitled “Si Rubah Tukang Usil”. This book tells the story of a fox who likes to be nosy to other forest dwellers and aims as an educational medium for early childhood in instilling good morals to fellow friends. The positive impact of this storybook is expected to strengthen good moral values, especially in the social context in the child's environment. This research also confirms the importance of educational media based on illustrated stories as an effective tool for teaching morals to children, because they more easily understand positive messages through interesting and illustrative narratives.